Imagining new legalities privacy and its possibilities in the 21st century - Sarat, Austin; Douglas, Lawrence; Umphrey, Martha Merrill (Stanford, Calif. : Stanford Law, 2012)
This book reminds us that examining the right to privacy and the public/private distinction is an important way of mapping the forms and limits of power that can legitimately be exercised by collective bodies over individuals and by governments over their citizens. It does not seek to provide a comprehensive overview of threats to privacy and rejoinders to them. Instead it considers several different conceptions of privacy and provides examples of legal inventiveness in confronting some contemporary challenges to the public/private distinction.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Privacy, Right of; Privacy, Right of -- United States; Law; Jurisprudence & general issues; Methods, theory & philosophy of law; Laws of specific jurisdictions & specific areas of law